(untitled) (American Journal of Society and Law, 2023)
The conscientious pursuit of crime prevention is a worthy objective of every criminal law and criminal justice system as a whole, and many evidences prove that law and order would break down in the absence of the criminal justice system. Withmuchemphasis onpunishment,however, victims of criminal offencesmore oftenbecome alienatedand end up getting immersed in a complex physical and psychological trauma under a criminal proceedingthat does not include them as a formal party. This paper presents adebate on whether the state is a better agent to pursue breaches of individual rights such as murder, rape, burglary, and theft, which are tagged as criminal offences. Or is the individual victim better equipped to decide on taking on the case for justice through either retribution or compensation?The paper examines the concept of punitive sanction throughthe postcolonial theory lens and argues forthe decolonization of the coloniallyinherited criminal law and a shift towards a System in which the victim is capable of being empowered by invoking processes that place him within proximity to criminal proceedings. This perspective questions the foundational assumption of the State ordered punishmentas intrinsic to the functions of the criminal justice system.There is a wide array of potential methodologies for studies of this nature, but this paper adopts a basic historical survey through secondary sources. The findings of the paper reveal that the pursuit of justice in all its nuanced forms will be much better served under a justice system that promotes the victim’s right to apply for compensation, damages and restitution in criminal cases through personal remedies.